Ideology and the Micro-foundations of CSR: Why Executives Believe in the Business Case for CSR and how this Affects their CSR Engagements - Hafenbrädl, Sebastian; Waeger, Daniel (Academy of Management Journal, 2017)
Existing research on executives’ belief in the business case for corporate social responsibility (CSR) is built on two premises. The first is that, in order to believe in the business case, executives need factual evidence that this business case indeed exists. The second premise is that those executives who do believe in the business case will readily invest in CSR-related activities. The results from our four studies tell a different story. We show that managers, rather than focusing on factual evidence, believe in the business case because they espouse a fair market ideology—the tendency to justify and idealize the market economy system. At the same time, even though managers espousing a fair market ideology believe in the business case for CSR, they are not more inclined to engage in CSR than managers who do not hold such an ideology, because they also experience weaker moral emotions when confronted with ethical problems. By drawing on system justification theory, we simultaneously explore antecedents and consequences of executives’ belief in the business case for CSR and of their moral emotions. In doing so, we help advance knowledge about the micro-foundations of CSR.